System analysis and design of BRAC miacro credit program - Kabir, Obaidul; Huq, Razwanul (BRAC University, 2010)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2005.